Odpowiedź:
a) 5+6x +( 4y-5x -3)= 5+6x +4y -5x -3= x +4y +2
b) 2u-4w + ( 7 -u +w)= 2u - 4w +7 -u +w= u -3w +7
c) 2a + ( 3a-2b) + (a+b)= 2a +3a -2b +a +b= 6a -b
d) 2 - 3s + ( 2 - 3s+4t ) +( 1+6s)= 2 - 3s +2 -3s +4t +1 +6s= 4t+5
e) 5m+3n -5 - (2m-3n -5)= 5m +3n -5 -2m +3n +5= 3m +6n
f) 3 - ( 4a-6b)+ ( 2 - a -7b)= 3 -4a +6b+2 -a -7b= - 5a -b+5
g) -2c +4 - ( 3c+2d ) - (5d-2)= -2c +4 -3c -2d -5d +2= -5c -7d+6
h) 8p - ( 3-4p -r) - ( 2 +3p +5r)= 8p -3 +4p +r -2 -3p -5r= 9p -4r-5
Szczegółowe wyjaśnienie: